A simulation study of thermal and mechanical properties of brake pads using different type of materials - Idid S.M.S.; Isa M.R.; Zaroog O.S.; Jalal M.F.A.; Sulaiman S.N.; Zahari N.M. (American Institute of Physics Inc., 2023)
Modern vehicles require good performance of braking system as well as having a safe environment of the surrounding. The use of asbestos as conventional brake pad has been causing harmful effects to the environment due to its dust that has been released by the frictional contact between the disc rotor and the brake pad during braking. Alternative materials to replace asbestos as conventional brake pad have been conducted over recent years for a safer environment and better braking performance of the modern vehicles. As a method to test the potential of alternative materials, modern simulation software has been put to use. This study focuses the use of a modelling software known as PTC Creo Parametric and a simulation software known as ANSYS to test the properties of natural fibres, which are kenaf, coconut, palm and asbestos, to determine the potential of replacing asbestos as conventional brake pad. The materials considered for this thesis are kenaf, coconut, palm and asbestos. Factors that affect the material potentials have been taken into consideration which includes design of disc rotor and brake pad, material properties and thermal and mechanical effects. Technical setup has been obeyed to conduct the simulation task. In conclusion, the factors stated do affect the braking material potentials and kenaf is the most suitable material to replace asbestos as conventional brake pad among all materials stated. 2021 American Institute of Physics Inc.. All rights reserved.